2021
DOI: 10.3390/su14010276
|View full text |Cite
|
Sign up to set email alerts
|

Does the Past Affect the Future? An Analysis of Consumers’ Dining Intentions towards Green Restaurants in the UK

Abstract: Due to the growing notion of environmental protection, many restaurants have started to apply operational practices to diminish their carbon footprint, leading to the emergence of “green” restaurants. Green restaurants are establishments committed to minimizing adverse environmental consequences throughout their operations. Nevertheless, further research is warranted to examine consumer behavior in this field. Taking the consumers’ perspective, this study uses an augmented theory of planned behavior (TPB) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This result means that customers must move out and eat out on their own to visit restaurants and to use take-out services, which strengthens perceived behavioral control such as washing hands and wearing masks, thereby lowering their behavioral intention to dine out. According to Ajzen [44], people intend to perform an action according to the degree to which they believe they have control over an action, so under the pandemic, customers' control behaviors related to dining-out activities, such as compliance with personal hygiene, unnecessary refraining from going out, and refraining contact with others, and it can be said that customers' perceived behavioral control influenced the intention to behave [58,59]. Third, in this study, the types of dining-out activities were subdivided and the differences in each subdivided dining-out activity before and after the pandemic were compared and analyzed, which is also a significant contribution.…”
Section: Academic Implicationsmentioning
confidence: 99%
“…This result means that customers must move out and eat out on their own to visit restaurants and to use take-out services, which strengthens perceived behavioral control such as washing hands and wearing masks, thereby lowering their behavioral intention to dine out. According to Ajzen [44], people intend to perform an action according to the degree to which they believe they have control over an action, so under the pandemic, customers' control behaviors related to dining-out activities, such as compliance with personal hygiene, unnecessary refraining from going out, and refraining contact with others, and it can be said that customers' perceived behavioral control influenced the intention to behave [58,59]. Third, in this study, the types of dining-out activities were subdivided and the differences in each subdivided dining-out activity before and after the pandemic were compared and analyzed, which is also a significant contribution.…”
Section: Academic Implicationsmentioning
confidence: 99%
“…To address this supply chain concept, this research focuses on conducting an empirical review of the food service industry in the UAE. In order to achieve higher customer satisfaction and business competitiveness, this research specifies order winners for the food service industry (Alshurideh, 2014;Shishan et al, 2021). Order winners are standards that distinguish a company's products or services from another company with respect to the fact that lean and agile paradigms should be selected according to marketplace requirements (Martin & Towill, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some scholars argue that the literature exploring the relationships between sustainability and restaurants is still at initial stage (Tommasetti et al, 2018) and often emphasizing the environmental dimension rather than the social and economic aspects of sustainability, which compromises its holist approach (Higgins-Desbiolles et al, 2017). In addition, one of the focus of current research is on consumers and their perceptions of green attributes, intentions and choices in restaurants (Shishan et al, 2022;Han et al, 2020;Nicolau et al, 2020;Yu et al, 2018;Filimonau et al, 2018;Kwok et al, 2016;DiPietro & Gregory, 2013;Dewald et al, 2013;Hu et al, 2010;Schubert et al, 2010;Dutta et al, 2008). Furthermore, in terms of cultural e national contexts, the studies have concentrated on the following countries: USA (DiPietro & Gregory, 2013;DiPietro et al, 2013a;DiPietro et al, 2013b;Dewald et al, 2013;Schubert et al, 2010), South Korea (Han et al, 2020;Kim et al, 2019), China (Yu et al, 2018), Taiwan (Hu et al, 2010), Greece (Karagiannis & Andrinos, 2021), UK (Shishan et al, 2022), Poland (Filimonau et al, 2018), Italy (Tommasetti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the focus of current research is on consumers and their perceptions of green attributes, intentions and choices in restaurants (Shishan et al, 2022;Han et al, 2020;Nicolau et al, 2020;Yu et al, 2018;Filimonau et al, 2018;Kwok et al, 2016;DiPietro & Gregory, 2013;Dewald et al, 2013;Hu et al, 2010;Schubert et al, 2010;Dutta et al, 2008). Furthermore, in terms of cultural e national contexts, the studies have concentrated on the following countries: USA (DiPietro & Gregory, 2013;DiPietro et al, 2013a;DiPietro et al, 2013b;Dewald et al, 2013;Schubert et al, 2010), South Korea (Han et al, 2020;Kim et al, 2019), China (Yu et al, 2018), Taiwan (Hu et al, 2010), Greece (Karagiannis & Andrinos, 2021), UK (Shishan et al, 2022), Poland (Filimonau et al, 2018), Italy (Tommasetti et al, 2018). Few comparative and cross-national studies have been found as the ones analyzing India and the USA (Dutta et al, 2008) and Poland and Lithuania (Trafialek et al, 2020), supporting the call by some authors for further research in other countries and cultural contexts (Kim et al, 2019;Hu et al, 2010), as well as comparative and cross-national studies (T. M.…”
Section: Introductionmentioning
confidence: 99%